2013
DOI: 10.7567/jjap.52.09kd01
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structural Analyses of Ferrielectric Tetragonal (Bi1/2Na1/2)TiO3–7%BaTiO3 Powders and Single Crystals

Abstract: We have investigated the crystal structure of (Bi1/2Na1/2)TiO3–7%BaTiO3 (BNT–7%BT) by high-resolution neutron powder diffraction (NPD) and high-energy synchrotron radiation X-ray diffraction (SR-XRD) analyses. The NPD study revealed that the BNT–7%BT crystals have a single-phase tetragonal structure with P4b m symmetry. The crystal structure refined by the Rietveld method was found to be similar to the ferrielectric P4b m phase reported for BNT at a high temperature of 673 K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 45 publications
2
33
0
Order By: Relevance
“…Unlike antiferroelectrics with a remanent polarization ( P r ) of zero25, the crystals have a certain P r . This apparent P r associated with the pinched hysteresis suggests that the crystals have the ferrielectric phase in space group P 4 bm at E  = 0, as revealed for BNT–7%BT powders by neutron diffraction structural analysis26.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…Unlike antiferroelectrics with a remanent polarization ( P r ) of zero25, the crystals have a certain P r . This apparent P r associated with the pinched hysteresis suggests that the crystals have the ferrielectric phase in space group P 4 bm at E  = 0, as revealed for BNT–7%BT powders by neutron diffraction structural analysis26.…”
Section: Resultsmentioning
confidence: 71%
“…In the poled state at E  = 0 kV/cm (Fig. 2a), all diffraction spots arise from a ferrielectric tetragonal structure in space group P 4 bm 222627. Among the fundamental hkl reflections from the pseudocubic cell, we detect 1/2{ o o e } superlattice reflections, where o denotes an odd number and e an even number.…”
Section: Resultsmentioning
confidence: 89%
“…3(a)], and the P r value (13.3 C/cm 2 ) of the film is clearly large as compared to that of bulk P4bm phase. The induction of this large P r is likely to be linked to the fact that the crystal lattice of the P4bm phase of the film is distorted to a greater extent along the c -axis direction compared than in the bulk NBT–BT, i.e., the ( c / a ) pc of the film is 1.004, whereas the most accepted value for bulk is less than 1.001 46,47 . It is most likely that the distortion of the crystal lattice results not only from compressive stress caused by energetic particle bombardment in sputtering but also from deposition-induced defects such as defect dipoles 48 .…”
Section: Resultsmentioning
confidence: 99%
“…Transmission electron microscopy observations by Ma et al [28] have revealed that (1 − x)BNT-xBT ceramics without an application of E exhibit P4bm symmetry in the x range of 6%-10%. Neutron powder diffraction study conducted by Kitanaka et al [79] have reported direct evidence of tetragonal P4bm for BNT-7%BT powder. The P4bm phase has a P s of 4 μC/cm 2 [79] along <001> pc , as depicted in Figure 3b.…”
Section: +mentioning
confidence: 99%
“…Neutron powder diffraction study conducted by Kitanaka et al [79] have reported direct evidence of tetragonal P4bm for BNT-7%BT powder. The P4bm phase has a P s of 4 μC/cm 2 [79] along <001> pc , as depicted in Figure 3b. It is suggested that the MPB between monoclinic Cc and tetragonal P4bm lies around x of 6%.…”
Section: +mentioning
confidence: 99%